An in vitro Propagation of Aspilia africana (Pers.) C. D. Adams, and Evaluation of Its Anatomy and Physiology of Acclimatized Plants - Okello, Denis; Yang, Sungyu; Komakech, Richard; Rahmat, Endang; Chung, Yuseong; Gang, Roggers; Kim, Yong-Goo; Omujal, Francis; Kang, Youngmin (Frontiers in Plant Science, 2021)
Aspilia africana (Pers.) C. D. Adams is an important medicinal plant that has been used for generations in many African countries to treat various health problems, including inflammatory conditions, osteoporosis, tuberculosis, cough, measles, diabetes, diarrhea, malaria, and wounds. We developed an efficient repeatable protocol for in vitro regeneration of A. africana from nodal segment explants. We assessed the effects of plant media on A. africana growth, cytokinins for in vitro shoot regeneration and proliferation, and auxins for the rooting of regenerated shoots. Furthermore, chlorophyll content, photosynthetic rates, anatomy (leaves, stems, and roots), and Fourier transform near-infrared (FT-NIR) spectra (leaves, stems, and roots) of the in vitro regenerated and maternal A. africana plants were compared. Murashige and Skoog media, containing vitamins fortified with benzylaminopurine (BAP, 1.0 mg/l), regenerated the highest number of shoots (13.0 ± 0.424) from A. africana nodal segments. 1-naphthaleneacetic acid (NAA, 0.1 mg/l) produced up to 13.10 ± 0.873 roots, 136.35 ± 4.316 mm in length, and was the most efficient for rooting. During acclimatization, the in vitro regenerated A. africana plants had a survival rate of 95.7%, displaying normal morphology and growth features. In vitro regenerated and mother A. africana plants had similar chlorophyll contents, photosynthetic rates, stem and root anatomies, and FT-NIR spectra of the leaf, stem, and roots. The established regeneration protocol could be used for large-scale multiplication of the plant within a short time, thus substantially contributing to its rapid propagation and germplasm preservation, in addition to providing a basis for the domestication of this useful, high-value medicinal plant.